Storage-resistant modified A-stage phenolic resin and preparation method thereof
By adding boric acid to the formaldehyde phenolic resin, the content of phenolic hydroxyl groups is reduced and the three-dimensional network structure is formed, the problem of low storage stability of resylene phenolic resin is solved, and the toughness and mechanical properties of the resin are improved.
Patent Information
- Application Number
- CN202411949310.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
Resinol is prone to self-polymerization during storage, resulting in a decrease in storage stability.
By adding boric acid to the formaldehyde phenolic resin, it reacts with the phenolic hydroxyl group, reducing the phenolic hydroxyl content, and introducing boron atoms to form flexible B-O bonds and three-dimensional network structures, improving the toughness and mechanical properties of the resin.
The storage stability and mechanical properties of the modified resylene phenolic resin are improved, and the toughness and interface bonding strength of the resin are enhanced.
Smart Images

Figure BDA0005214469190000071 
Figure BDA0005214469190000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a storage-resistant modified resol phenolic resin and a preparation method thereof. Background Art
[0002] Resol phenolic resin is widely used in adhesives, composite materials and other fields due to its excellent heat resistance, adhesion, electrical insulation and other characteristics. In particular, resol phenolic resin has been rapidly developed in the fields of sand casting.
[0003] However, the large amount of hydroxymethyl in the resol phenolic resin makes it easy for the resol phenolic resin to undergo self-polymerization during storage, thereby reducing the storage stability of the resol phenolic resin. Summary of the invention
[0004] In order to improve the storage stability of the modified resol phenolic resin, the present application provides a storage-resistant modified resol phenolic resin and a preparation method thereof.
[0005] In the first aspect, the storage-resistant modified resol phenolic resin provided by the present application adopts the following technical solution: A storage-resistant modified resol phenolic resin comprises the following raw materials in parts by mass: 160-180 parts of formaldehyde, 100-120 parts of phenol, 35-45 parts of boric acid and 24-28 parts of ammonia water.
[0006] By adopting the above technical solution, boric acid is added to the formaldehyde phenolic resin, so that the storage stability of the modified resol phenolic resin is improved.
[0007] Boric acid reacts with phenolic hydroxyl groups, thereby reducing the phenolic hydroxyl groups in the system and further improving the storage stability of the modified resol phenolic resin.
[0008] In addition, boron atoms are introduced into the system. The flexible BO bonds can improve the toughness of the modified resol phenolic resin, and the boron element forms a three-dimensional network structure through self-crosslinking, thereby improving the mechanical properties of the modified resol phenolic resin.
[0009] Preferably, the invention further comprises 18-24 parts of reinforcing agent, wherein the reinforcing agent comprises potassium titanate whisker and basalt fiber.
[0010] By adopting the above technical solution, the basalt fiber has higher strength and elastic modulus, so adding the basalt fiber to the modified resol phenolic resin can improve the mechanical properties of the modified resol phenolic resin.
[0011] Potassium titanate whiskers are interspersed between the resin matrix and the basalt fibers, so that the potassium titanate whiskers can bridge the resin matrix and the basalt fibers, thereby enhancing the interfacial bonding strength between the basalt fibers and the resin matrix.
[0012] In addition, potassium titanate whiskers have high strength and high modulus, which can further improve the mechanical properties of modified resol phenolic resin.
[0013] Preferably, the mass ratio of the potassium titanate whiskers to the basalt fibers is 1:(0.2-0.4).
[0014] By adopting the above technical solution and controlling the mass ratio of potassium titanate whiskers to basalt fibers within the above range, the mechanical properties of the modified resol phenolic resin can be effectively improved.
[0015] Preferably, the potassium titanate whiskers are prepared by the following modification steps: S100, adding a silane coupling agent to an ethanol aqueous solution, adjusting the pH to 1.5 with glacial acetic acid, and stirring to obtain a silane coupling agent hydrolyzate; S200, adding potassium titanate whiskers into anhydrous ethanol, then adding silane coupling agent hydrolyzate, stirring sufficiently, filtering, washing, and drying in sequence to obtain modified potassium titanate whiskers.
[0016] By adopting the above technical solution, potassium titanate whiskers are very easy to agglomerate due to their fine size. At the same time, the surface of potassium titanate whiskers is hydrophilic and oleophobic. When they are directly compounded into the resin matrix system, the bonding force between them and the resin matrix is poor.
[0017] The silane coupling agent is hydrolyzed to form silanol groups, which react with the hydroxyl groups on the surface of potassium titanate whiskers to form hydrogen bonds. At the same time, the silanols of each silane molecule associate and aggregate to form a network structure film covering the surface of potassium titanate whiskers, making the potassium titanate whiskers organic, thereby reducing the polarity of the surface of potassium titanate whiskers, reducing the surface energy of potassium titanate whiskers, enhancing the bonding force between potassium titanate whiskers and the resin matrix, and reducing the interfacial tension between potassium titanate whiskers and the resin matrix.
[0018] Preferably, the mass ratio of the potassium titanate whisker to the silane coupling agent is 1:(0.03-0.07).
[0019] By adopting the above technical solution and controlling the mass ratio of potassium titanate whiskers to silane coupling agent within the above range, the interfacial tension between the potassium titanate whiskers and the resin matrix can be effectively improved.
[0020] Preferably, the potassium titanate whisker is pretreated before the modification and preparation process, and the potassium titanate whisker pretreatment comprises the following steps: Potassium titanate whiskers are added into deionized water, stirred thoroughly and placed in a constant temperature water bath, and then sodium silicate aqueous solution and sulfuric acid aqueous solution are added until the pH value reaches 9.5. After heat preservation and aging, the pretreated potassium titanate whiskers are filtered, washed and dried in sequence to obtain pretreated potassium titanate whiskers.
[0021] By adopting the above technical scheme, sodium silicate generates orthosilicic acid or silicate polymer, and the orthosilicic acid or silicate polymer is bonded to the hydroxyl group on the surface of the potassium titanate whisker. Then, under the continuous polymerization, a solid silicon dioxide film is formed on the surface of the potassium titanate whisker, so that the surface of the pretreated potassium titanate whisker is rich in hydroxyl groups, which is conducive to the modification of the potassium titanate whisker by the silane coupling agent, thereby making the potassium titanate whisker more compatible with the resin matrix.
[0022] Preferably, the modification preparation method of basalt fiber comprises the following steps: The silane coupling agent is added into the ethanol aqueous solution, and after being fully stirred, the basalt fiber is added, and after being soaked, the fiber is taken out, and then dried after being naturally dried to obtain the modified basalt fiber.
[0023] By adopting the above technical scheme, hydroxyl groups are formed on the surface of basalt fiber after absorbing water, and at the same time, silanol is hydrolyzed to form silanol, and the hydrolyzed silanol forms hydrogen bonds with the hydroxyl groups on the surface of basalt fiber, and hydrogen bonds are formed between silanol molecules. Therefore, under the action of silane coupling agent, the surface of basalt fiber has higher surface energy, so that the wettability and adhesion of basalt fiber to resin matrix are effectively improved, thereby improving the interface performance between basalt fiber and resin matrix.
[0024] After the basalt fiber is surface treated with silane coupling agent, the surface roughness of the basalt fiber is significantly improved, thereby improving the interface bite force between the basalt fiber and the resin matrix.
[0025] Preferably, the mass ratio of the basalt fiber to the silane coupling agent is 1:(0.4-0.6).
[0026] By adopting the above technical solution and controlling the mass ratio of basalt fiber to silane coupling agent within the above range, the interface performance between basalt fiber and resin matrix can be effectively improved.
[0027] In a second aspect, the present application provides a method for preparing a storage-resistant modified resol phenolic resin as in the first aspect, which adopts the following technical scheme: A method for preparing a storage-resistant modified resol phenolic resin comprises the following steps: Ammonia water is added to phenol, and after the temperature is raised, formaldehyde is added, the temperature is continued to be raised and constant temperature treatment is performed, decompression and dehydration are performed, and then boric acid is added, and the constant temperature treatment is continued and decompression and dehydration are performed again to obtain a modified resol phenolic resin.
[0028] By adopting the above technical scheme, phenol and formaldehyde are reacted under the condition of ammonia water to generate salicylic alcohol, and then boric acid is added after decompression and dehydration, and salicylic alcohol reacts with boric acid to finally obtain boron phenolic resin.
[0029] In summary, the present application includes at least one of the following beneficial technical effects: 1. Boric acid reacts with phenolic hydroxyl groups, thereby reducing the phenolic hydroxyl groups in the system and improving the storage stability of the modified resol phenolic resin. In addition, boron atoms are introduced into the system. The flexible BO bonds can improve the toughness of the modified resol phenolic resin, and the boron element forms a three-dimensional network structure through self-crosslinking, thereby improving the mechanical properties of the modified resol phenolic resin.
[0030] 2. Both basalt fiber and potassium titanate whisker have high strength and elastic modulus, and potassium titanate whisker is interspersed between phenolic resin matrix and basalt fiber, so that potassium titanate whisker can bridge the resin matrix and basalt fiber, thereby enhancing the interfacial bonding strength between basalt fiber and resin matrix, thereby improving the mechanical properties of modified resol phenolic resin. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in conjunction with examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0032] Example 1 The modified resol phenolic resin includes the following raw materials by weight: 170 g of formaldehyde, 110 g of phenol, 40 g of boric acid, and 26 g of ammonia water.
[0033] The preparation method of modified resol phenolic resin comprises the following steps: Ammonia water was added to phenol, and the temperature was raised to 60°C. After the phenol was completely dissolved, formaldehyde was added, and the temperature was continued to be raised to 90°C, and the temperature was kept constant for 80 minutes, and then dehydrated under reduced pressure. Boric acid was added and the temperature was kept constant for 100 minutes, and then dehydrated under reduced pressure again to obtain a modified resol phenolic resin.
[0034] Example 2 The modified resol phenolic resin includes the following raw materials by weight: 160 g of formaldehyde, 100 g of phenol, 35 g of boric acid, 24 g of ammonia water, and 18 g of a reinforcing agent.
[0035] The reinforcing agents include potassium titanate whiskers and basalt fibers, and the mass ratio of potassium titanate whiskers to basalt fibers is 1:0.2.
[0036] The preparation method of modified resol phenolic resin comprises the following steps: S1, adding ammonia water to phenol, heating to 60°C, after phenol is completely dissolved, adding 2 / 3 of formaldehyde, continuing to heat to 90°C, adding potassium titanate whiskers and keeping the temperature constant for 20 minutes, then adding the remaining formaldehyde, keeping the temperature constant for 80 minutes, decompressing and dehydrating, adding boric acid and keeping the temperature constant for 100 minutes, and decompressing and dehydrating again to obtain a primary modified resol phenolic resin; S2. The primary modified resol phenolic resin is crushed and added together with basalt fiber into 300 g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 80%), and then placed in a ventilated place for drying for 48 hours, and then placed in an oven at 120° C. for drying for 30 minutes, and then loaded into a homemade mold, and the modified resol phenolic resin is prepared by a compression molding process.
[0037] Example 3 The modified resol phenolic resin includes the following raw materials by weight: 180 g of formaldehyde, 120 g of phenol, 45 g of boric acid, and 28 g of ammonia water.
[0038] The reinforcing agents include potassium titanate whiskers and basalt fibers, and the mass ratio of potassium titanate whiskers to basalt fibers is 1:0.4.
[0039] The preparation method of modified resol phenolic resin comprises the following steps: S1, adding ammonia water to phenol, heating to 60°C, after phenol is completely dissolved, adding 2 / 3 of formaldehyde, continuing to heat to 90°C, adding potassium titanate whiskers and keeping the temperature constant for 20 minutes, then adding the remaining formaldehyde, keeping the temperature constant for 80 minutes, decompressing and dehydrating, adding boric acid and keeping the temperature constant for 100 minutes, and decompressing and dehydrating again to obtain a primary modified resol phenolic resin; S2. The primary modified resol phenolic resin is crushed and added together with basalt fiber into 300 g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 80%), and then placed in a ventilated place for drying for 48 hours, and then placed in an oven at 120° C. for drying for 30 minutes, and then loaded into a homemade mold, and the modified resol phenolic resin is prepared by a compression molding process.
[0040] Example 4 The modified resol phenolic resin includes the following raw materials by weight: 170 g of formaldehyde, 110 g of phenol, 40 g of boric acid, 26 g of ammonia water, and 21 g of a reinforcing agent.
[0041] The reinforcing agents include potassium titanate whiskers and basalt fibers, and the mass ratio of potassium titanate whiskers to basalt fibers is 1:0.3.
[0042] The preparation method of modified resol phenolic resin comprises the following steps: S1, adding ammonia water to phenol, heating to 60°C, after phenol is completely dissolved, adding 2 / 3 of formaldehyde, continuing to heat to 90°C, adding potassium titanate whiskers and keeping the temperature constant for 20 minutes, then adding the remaining formaldehyde, keeping the temperature constant for 80 minutes, decompressing and dehydrating, adding boric acid and keeping the temperature constant for 100 minutes, and decompressing and dehydrating again to obtain a primary modified resol phenolic resin; S2. The primary modified resol phenolic resin is crushed and added together with basalt fiber into 300 g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 80%), and then placed in a ventilated place for drying for 48 hours, and then placed in an oven at 120° C. for drying for 30 minutes, and then loaded into a homemade mold, and the modified resol phenolic resin is prepared by a compression molding process.
[0043] Example 5 The difference between Example 5 and Example 4 is that the mass ratio of potassium titanate whiskers to basalt fibers is 1:0.1.
[0044] Example 6 The difference between Example 6 and Example 4 is that the mass ratio of potassium titanate whiskers to basalt fibers is 1:0.5.
[0045] Example 7 The difference between Example 7 and Example 4 is that the potassium titanate whiskers are prepared by the following modification steps: S100, adding 3 g of silane coupling agent to 300 g of ethanol aqueous solution (the mass concentration of the ethanol aqueous solution is 90%), adjusting the pH to 1.5 with glacial acetic acid, and then electromagnetically stirring at 30° C. for 60 min to obtain a silane coupling agent hydrolyzate; S200, add 100g potassium titanate whisker to 1000g anhydrous ethanol, then add silane coupling agent hydrolyzate, stir at 60°C for 2h, filter, wash with anhydrous ethanol, put in an oven at 120°C and dry for 5h to obtain modified potassium titanate whisker.
[0046] Wherein, the silane coupling agent is KH-570.
[0047] Example 8 The difference between Example 8 and Example 4 is that the potassium titanate whiskers are prepared by the following modification steps: S100, adding 7 g of silane coupling agent to 300 g of ethanol aqueous solution (the mass concentration of the ethanol aqueous solution is 90%), adjusting the pH to 1.5 with glacial acetic acid, and then electromagnetically stirring at 30° C. for 60 min to obtain a silane coupling agent hydrolyzate; S200, add 100g potassium titanate whisker to 1000g anhydrous ethanol, then add silane coupling agent hydrolyzate, stir at 60°C for 2h, filter, wash with anhydrous ethanol, put in an oven at 120°C and dry for 5h to obtain modified potassium titanate whisker.
[0048] Wherein, the silane coupling agent is KH-570.
[0049] Example 9 The difference between Example 9 and Example 4 is that the potassium titanate whiskers are prepared by the following modification steps: S100, adding 5 g of silane coupling agent to 300 g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 90%), adjusting the pH to 1.5 with glacial acetic acid, and then electromagnetically stirring at 30° C. for 60 min to obtain a silane coupling agent hydrolyzate; S200, add 100g potassium titanate whisker to 1000g anhydrous ethanol, then add silane coupling agent hydrolyzate, stir at 60°C for 2h, filter, wash with anhydrous ethanol, put in an oven at 120°C and dry for 5h to obtain modified potassium titanate whisker.
[0050] Wherein, the silane coupling agent is KH-570.
[0051] Example 10 The difference between Example 10 and Example 9 is that during the modification and preparation process of potassium titanate whiskers, the mass ratio of potassium titanate whiskers to silane coupling agent is 1:0.02.
[0052] Embodiment 11 The difference between Example 11 and Example 9 is that during the modification and preparation process of potassium titanate whiskers, the mass ratio of potassium titanate whiskers to silane coupling agent is 1:0.08.
[0053] Example 12 The difference between Example 12 and Example 9 is that the potassium titanate whisker is pretreated before the modification and preparation process, and the potassium titanate whisker pretreatment includes the following steps: 10 g of potassium titanate whiskers were added to 100 g of deionized water, ultrasonically dispersed for 20 minutes, and then placed in a constant temperature water bath at 85°C. Then, sodium silicate aqueous solution (the mass concentration of sodium silicate aqueous solution was 0.2 mol / L) and sulfuric acid aqueous solution (the mass concentration of sulfuric acid aqueous solution was 1%) were added until the pH reached 9.5. After heat aging for 2 hours, the pretreated potassium titanate whiskers were filtered, washed, and dried in sequence to obtain pretreated potassium titanate whiskers.
[0054] Example 13 The difference between Example 13 and Example 12 is that the basalt fiber is prepared by the following modification steps: 4 g of silane coupling agent was added to 100 g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution was 50%), and after being fully stirred for 30 min, 10 g of basalt fiber was added, and after being soaked for 30 min, it was taken out, naturally dried at 25 ° C, and then placed in an oven at 120 ° C for 1 h to obtain modified basalt fiber.
[0055] The silane coupling agent is KH-550.
[0056] Embodiment 14 The difference between Example 14 and Example 12 is that the basalt fiber is prepared by the following modification steps: 6 g of silane coupling agent was added to 100 g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution was 50%), and after being fully stirred for 30 min, 10 g of basalt fiber was added, and after being soaked for 30 min, it was taken out, naturally dried at 25 ° C, and then placed in an oven at 120 ° C for 1 h to obtain modified basalt fiber.
[0057] The silane coupling agent is KH-550.
[0058] Embodiment 15 The difference between Example 15 and Example 12 is that the basalt fiber is prepared by the following modification steps: 5 g of silane coupling agent was added to 100 g of ethanol aqueous solution (the mass concentration of ethanol aqueous solution was 50%), and after being fully stirred for 30 min, 10 g of basalt fiber was added, and after being soaked for 30 min, it was taken out, naturally dried at 25 ° C, and then placed in an oven at 120 ° C for 1 h to obtain modified basalt fiber.
[0059] The silane coupling agent is KH-550.
[0060] Example 16 The difference between Example 16 and Example 15 is that the mass ratio of basalt fiber to silane coupling agent is 1:0.2.
[0061] Embodiment 17 The difference between Example 17 and Example 15 is that the mass ratio of basalt fiber to silane coupling agent is 1:0.8.
[0062] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no boric acid is added to the resol phenolic resin for modification.
[0063] Comparative Example 2 The difference between Comparative Example 2 and Example 4 is that the reinforcing agent contains only basalt fibers.
[0064] Comparative Example 3 The difference between Comparative Example 3 and Example 4 is that the reinforcing agent contains only potassium titanate whiskers.
[0065] Performance Testing The samples prepared in Examples 1-17 and Comparative Examples 1-3 were sampled and subjected to the following performance tests.
[0066] 1. Storage performance test According to GB / T14074-2006, the storage performance of the samples was tested at room temperature. Three parallel experiments were performed and the results were averaged.
[0067] 2. Mechanical properties test (1) Tensile strength The tensile strength of the sample was tested at room temperature using a Z050 electronic tensile testing machine in accordance with the standard GB / T1447-2005. Three parallel experiments were performed at the same time, and the results were averaged. The tensile speed was 10 mm / min.
[0068] (2) Impact strength According to GB / T1843-2008 standard, the unnotched impact strength was measured on a ZBC-1251 pendulum impact testing machine. Three parallel experiments were performed at the same time, and the results were averaged.
[0069] Table 1 Data analysis Specifically, in combination with the test results of Examples 2-4 and Example 1, the tensile strength of Examples 2-4 is 25.58-25.72 MPa, and the impact strength is 7.32-7.43 kJ / m 2 The tensile strength of Example 1 is 21.35 MPa and the impact strength is 5.78 kJ / m 2 , it can be seen that the mechanical properties of Example 2-4 are better than those of Example 1, and the analysis is as follows: The difference between Example 2-4 and Example 1 is that potassium titanate whiskers and basalt fibers are added to the modified resol phenolic resin, both of which have high strength and high modulus, and the potassium titanate whiskers are interspersed between the phenolic resin matrix and the basalt fibers, so that the potassium titanate whiskers can bridge the resin matrix and the basalt fibers, thereby enhancing the interfacial bonding strength between the basalt fibers and the resin matrix, thereby improving the mechanical properties of the modified resol phenolic resin.
[0070] Specifically, in combination with the test results of Examples 7-9 and Example 4, the tensile strength of Examples 7-9 is 29.32-29.57 MPa, and the impact strength is 9.03-9.12 kJ / m 2 The tensile strength of Example 4 is 25.72MPa and the impact strength is 7.43kJ / m 2 , it can be seen that the mechanical properties of Examples 7-9 are better than those of Example 4, and the analysis is as follows: The difference between Examples 7-9 and Example 4 is that the potassium titanate whiskers are modified by a silane coupling agent, so that the potassium titanate whiskers are organic, which enhances the bonding force between the potassium titanate whiskers and the resin matrix, thereby improving the mechanical properties of the modified resol phenolic resin.
[0071] Specifically, in combination with the test results of Example 12 and Example 9, the tensile strength of Example 12 is 30.48 MPa and the impact strength is 10.59 kJ / m 2 The tensile strength of Example 4 is 29.57 MPa and the impact strength is 9.12 kJ / m 2 , it can be seen that the mechanical properties of Example 12 are better than those of Example 9, and the analysis is as follows: The difference between Example 12 and Example 9 is that the surface of the pretreated potassium titanate whiskers is rich in hydroxyl groups, which is conducive to the modification of the potassium titanate whiskers by the silane coupling agent, so that the potassium titanate whiskers can be better compatible with the resin matrix, thereby improving the mechanical properties of the modified resol phenolic resin.
[0072] Specifically, in combination with the test results of Examples 13-15 and Example 12, the tensile strength of Examples 13-15 is 34.78-34.95 MPa, and the impact strength is 12.33-12.47 kJ / m 2 The tensile strength of Example 12 is 30.48 MPa and the impact strength is 10.59 kJ / m 2 , it can be seen that the mechanical properties of Examples 13-15 are better than those of Example 12, and the analysis is as follows: The difference between Examples 13-15 and Example 12 is that the basalt fiber is modified by a silane coupling agent so that the surface of the basalt fiber has a higher surface energy and roughness, thereby improving the interface performance between the basalt fiber and the resin matrix, and then improving the mechanical properties of the modified resol phenolic resin.
[0073] Specifically, in combination with the test results of Example 1 and Comparative Example 1, the viscosity of Example 1 is 37mpa.s, the storage period is 180d, the tensile strength is 21.35MPa, and the impact strength is 5.78kJ / m 2 The viscosity of comparative example 1 is 49mpa.s, the storage period is 120d, the tensile strength is 15.78MPa, and the impact strength is 2.18kJ / m 2 , it can be seen that the storage resistance and mechanical properties of Example 3 are better than those of Comparative Example 1, and the analysis is as follows: the difference between Example 1 and Comparative Example 1 is that: the modified resol phenolic resin contains boric acid. On the one hand, boric acid reacts with phenolic hydroxyl groups to reduce the content of phenolic hydroxyl groups in the system, thereby improving the storage stability of the modified resol phenolic resin; on the other hand, boron atoms are also introduced into the system to improve the toughness of the resol phenolic resin, and the boron element forms a three-dimensional network structure through self-crosslinking, thereby having a positive effect on improving the mechanical properties of the modified resol phenolic resin.
[0074] Specifically, in combination with the test results of Example 4 and Comparative Example 2, the tensile strength of Example 4 is 25.72 MPa and the impact strength is 7.43 kJ / m 2The tensile strength of comparative example 2 is 23.18MPa and the impact strength is 6.17kJ / m 2 , it can be seen that the mechanical properties of Example 4 are better than those of Comparative Example 2, and the analysis is as follows: The difference between Example 4 and Comparative Example 2 is that the reinforcing agent contains potassium titanate whiskers in addition to basalt fibers. Potassium titanate whiskers can bridge the resin matrix and the basalt fibers, thereby enhancing the interfacial bonding strength between the basalt fibers and the resin matrix, thereby improving the mechanical properties of the modified resol phenolic resin.
[0075] Specifically, in combination with the test results of Example 4 and Comparative Example 3, the tensile strength of Example 4 is 25.72 MPa and the impact strength is 7.43 kJ / m 2 The tensile strength of comparative example 3 is 23.29MPa and the impact strength is 6.22kJ / m 2 , it can be seen that the mechanical properties of Example 4 are better than those of Comparative Example 3, and the analysis is as follows: The difference between Example 4 and Comparative Example 3 is that the reinforcing agent contains basalt fibers in addition to potassium titanate whiskers. The potassium titanate whiskers can bridge the resin matrix and the basalt fibers, thereby enhancing the interfacial bonding strength between the basalt fibers and the resin matrix, thereby improving the mechanical properties of the modified resol phenolic resin.
[0076] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A storage-resistant modified resol phenolic resin, characterized in that: The invention comprises the following raw materials in parts by weight: 160-180 parts of formaldehyde, 100-120 parts of phenol, 35-45 parts of boric acid and 24-28 parts of ammonia water.
2. A storage-resistant modified resol phenolic resin according to claim 1, characterized in that: The invention also comprises 18-24 parts of reinforcing agent, wherein the reinforcing agent comprises potassium titanate whisker and basalt fiber.
3. A storage-resistant modified resol phenolic resin according to claim 2, characterized in that: The mass ratio of the potassium titanate whisker to the basalt fiber is 1:(0.2-0.4).
4. The storage-resistant modified resol phenolic resin according to claim 1, characterized in that: The potassium titanate whiskers are prepared by the following modification steps: S100, adding a silane coupling agent to an ethanol aqueous solution, adjusting the pH to 1.5 with glacial acetic acid, and stirring to obtain a silane coupling agent hydrolyzate; S200, adding potassium titanate whiskers into anhydrous ethanol, then adding silane coupling agent hydrolyzate, stirring sufficiently, filtering, washing, and drying in sequence to obtain modified potassium titanate whiskers.
5. A storage-resistant modified resol phenolic resin according to claim 4, characterized in that: The mass ratio of the potassium titanate whisker to the silane coupling agent is 1:(0.03-0.07).
6. A storage-resistant modified resol phenolic resin according to claim 4, characterized in that: The potassium titanate whisker is also pretreated before the modification and preparation process, and the potassium titanate whisker pretreatment includes the following steps: Potassium titanate whiskers are added into deionized water, stirred thoroughly and placed in a constant temperature water bath, and then sodium silicate aqueous solution and sulfuric acid aqueous solution are added until the pH value reaches 9.
5. After heat preservation and aging, the pretreated potassium titanate whiskers are filtered, washed and dried in sequence to obtain pretreated potassium titanate whiskers.
7. The storage-resistant modified resol phenolic resin according to claim 1, characterized in that: The modified preparation method of basalt fiber comprises the following steps: The silane coupling agent is added into the ethanol aqueous solution, and after being fully stirred, the basalt fiber is added, and after being soaked, the fiber is taken out, and then dried after being naturally dried to obtain the modified basalt fiber.
8. The storage-resistant modified resol phenolic resin according to claim 7, characterized in that: The mass ratio of the basalt fiber to the silane coupling agent is 1:(0.4-0.6).
9. A method for preparing the storage-resistant modified resol phenolic resin according to claim 1, characterized in that: The steps include: Ammonia water is added to phenol, and after the temperature is raised, formaldehyde is added, the temperature is continued to be raised and constant temperature treatment is performed, decompression and dehydration are performed, and then boric acid is added, and the constant temperature treatment is continued and decompression and dehydration are performed again to obtain a modified resol phenolic resin.